The Mandela Effect - Sagana, Marisa; Paraskevopoulou, Melina (Open Schools Journal for Open Science, 2025)
This paper explores the Mandela Effect, a phenomenon where large groups of people recall false or distorted memories. We trace its origins, examine both psychological explanations and alternative theories such as parallel universes, and provide popular examples from media and pop culture. The impact of the Mandela Effect on society, particularly through the internet and collective memory, is discussed to better understand the boundaries between perception and reality.